Quantitative Analysis of the China-Europe Railway Express: Measuring Transport Efficiency and Trade Elasticity - Lyu Junfeng; Mynjanova Gulzhakan Tlesovna; Tukembayeva Kyyal (Theoretical Hypotheses and Empirical Results, 2026)
Objective: This paper develops a quantitative assessment of the China-Europe Railway Express (CR Express) and the broader China–Central Asia–Europe overland corridor system, with the dual aim of measuring transport efficiency across competing routing architectures and estimating the elasticity of bilateral trade volumes with respect to corridor capacity, transit time, and cost. It moves beyond narrative accounts of the Belt and Road Initiative to anchor the discussion in verifiable throughput, modal share, and trade-growth data drawn from Chinese customs statistics, Kazakhstan's Association of Financiers (AFK), MOFCOM announcements, and corridor operators' reports covering the period 2018–2025. Methodology: The study employs a mixed quantitative case-study design combining descriptive longitudinal analysis, comparative corridor benchmarking, and indicative elasticity estimation. Throughput indicators (train pairs per day, TEU, tonnes), temporal performance metrics (transit time, transshipment duration, dwell time), unit cost differentials, and bilateral trade values are cross-referenced across three parallel routing architectures — the Northern Corridor via Russia and Belarus, the Middle Corridor via the Trans-Caspian International Transport Route (TITR), and the emerging Southern Corridor via the China–Kyrgyzstan–Uzbekistan (CKU) railway — and benchmarked against the historical trajectory of China–Central Asia trade, which rose from USD 49.6 billion in 2021 to USD 106.3 billion in 2025. Findings: The analysis yields four quantitative findings. First, CR Express throughput has scaled non-linearly: Central Asia rail freight grew 24.7% year-on-year in the first eight months of 2025, with 9,626 through-trains and Khorgos dry-port throughput rising 26.9% in the first half alone. Second, efficiency gains are measurable at the gauge-transition level, where container transshipment time at Khorgos fell from five hours to one, and Dostyk–Moiynty double-tracking increased theoretical throughput from 12 to 60 train pairs per day — a fivefold capacity expansion. Third, the Middle Corridor's fivefold cargo-volume growth in seven years (from 800,000 tonnes to approximately 4 million tonnes) occurred despite a persistent unit-cost penalty relative to the Northern Corridor, indicating that geopolitical risk premiums, rather than cost optimisation, are driving modal substitution. Fourth, indicative elasticity estimates suggest that the trade response to capacity expansion is positive but highly asymmetric across Central Asian states, with Kazakhstan's commodity-linked exports exhibiting low elasticity and Uzbekistan's manufacturing-import flows exhibiting high elasticity. Implications: The study contributes to the transport economics and Eurasian connectivity literatures by providing a structured quantitative baseline against which future corridor performance can be measured. For policymakers in Kazakhstan, it highlights that raw capacity expansion alone will not translate linearly into trade growth absent parallel investments in value-added processing, financial settlement infrastructure, and customs harmonisation. For corridor operators, it underscores the importance of redundancy and multi-routing in an environment where a single geopolitical shock — such as the September 2025 Polish airspace closure that stranded over 130 freight trains in Belarus — can recalibrate route economics within weeks.